Cork & Fuzz : spring cleaning - Chaconas, Dori, 1938- (Chaconas, Dori, 1938- Cork & Fuzz., 2015)
"When Cork tries to boss Fuzz into helping him clean up, both friends learn how to work--and play--together"--